Building material and preparation method
By optimizing the ratio and preparation methods of lightweight concrete materials, combining aggregates and light aggregates, the problem of insufficient structural strength of existing lightweight concrete materials is solved, and high-strength and appropriate density building materials are achieved, which significantly improves material performance and application prospects.
Patent Information
- Application Number
- CN202411928561.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
Due to the low density of existing lightweight concrete materials, the structural strength is insufficient and cannot reach the high strength level of ordinary concrete materials, resulting in the problem of not being able to take into account both density and strength.
By optimizing the ratio and preparation method of concrete raw materials, building materials with moderate density are prepared by combining aggregates and light aggregates.
The high strength and appropriate density of lightweight concrete materials have been achieved, breaking the limitations of density and strength in traditional technology that cannot be taken into account at the same time, and significantly improving the performance and application prospects of building materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of materials, and more specifically, particularly relates to a building material and a preparation method thereof. Background Art
[0002] In the field of contemporary construction engineering, building industrialization and green sustainable development have become an irreversible trend. Traditional construction methods have many disadvantages, such as long construction period, many wet operations on site, serious waste of resources and difficulty in quality control. These problems have prompted the construction industry to seek more efficient, environmentally friendly and reliable building materials and technical solutions. Lightweight concrete materials have emerged under this background and have received widespread attention.
[0003] With the acceleration of urbanization, the urban population density continues to increase, and the demand for residential and various functional buildings has risen sharply. In high-rise buildings and prefabricated building systems, the demand for lightweight building materials has become more urgent. Traditional concrete materials are heavy in themselves, which not only increases the overall weight of the building, posing huge challenges to the foundation and structural design, but also requires larger machinery and equipment and more manpower and material resources during transportation, hoisting and installation, resulting in a significant increase in construction costs and difficulty in improving construction efficiency. For example, in the production and assembly of prefabricated components in prefabricated buildings, the heavier concrete components limit the selection of hoisting equipment and the acceleration of construction progress.
[0004] The dual pressures of resources and the environment have also promoted the development of lightweight concrete materials. On the one hand, the large-scale exploitation of natural aggregates (such as sand and gravel) in the construction industry has led to increasingly serious problems such as resource shortages and ecological environmental damage. Lightweight concrete materials can use industrial waste (such as fly ash, slag, etc.), recycled aggregates (such as recycled particles of construction waste), etc. as part or all of the aggregate source, achieving efficient recycling of resources and reducing dependence on natural resources. On the other hand, in the entire life cycle of a building, energy consumption is mainly concentrated in the use stage, and the good thermal insulation performance of lightweight concrete materials helps to reduce the energy consumption of buildings. Its internal porous structure can effectively hinder the transfer of heat. Compared with traditional concrete materials, it can significantly improve the energy-saving effect of buildings and reduce greenhouse gas emissions, which is in line with the strategic goal of global green building development.
[0005] At the same time, the development of modern construction technology, such as high-precision mold manufacturing technology, automated production line technology, and advanced maintenance technology, provides technical support for the large-scale and standardized production of lightweight concrete parts. These technologies can ensure that lightweight concrete materials have high dimensional accuracy, quality stability, and production efficiency during the production process, thereby further promoting the application and popularization of lightweight concrete materials in the construction market. In summary, lightweight concrete materials, with their advantages in reducing the weight of buildings, improving construction efficiency, saving resources, protecting the environment, and improving the functional quality of buildings, occupy an extremely important position in the process of building industrialization and green building development. They have broad application prospects and the driving force for sustainable development. However, the current lightweight concrete materials have insufficient structural strength due to their low density and cannot reach the high strength level of ordinary concrete materials. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a building material and a preparation method to solve the problem that the concrete material in the prior art cannot ensure that both the material density and the structural strength are at a high level, that is, the industry currently believes that the improvement of the two material parameters will conflict with each other.
[0007] The purpose and effect of the building material and preparation method of the present invention are achieved by the following specific technical means:
[0008] A building material comprises the following components in parts by weight: 15-45 parts of silicate cement, 4-40 parts of mineral powder, 0-100 parts of fly ash, 0.2-2.4 parts of activator, 2-10 parts of foaming agent, 0.3-1 parts of water reducer, 0.2-0.4 parts of reinforcing agent, and 16-45 parts of water.
[0009] Furthermore, it also includes 0-100 parts of aggregate and 0-50 parts of light aggregate.
[0010] Furthermore, the aggregate includes but is not limited to 3-10 mm crushed stone, construction solid waste, graded sand, etc., and the light aggregate is expanded clay and clay sand.
[0011] Furthermore, the silicate cement is silicate cement with a grade of 42.5 or above.
[0012] Furthermore, the mineral powder is granulated blast furnace slag powder.
[0013] Furthermore, the fly ash is fine solid particles in the flue gas ash produced by coal combustion.
[0014] Furthermore, the activator is an alkaline activator.
[0015] Furthermore, the foaming agent is a composite foaming agent.
[0016] Furthermore, the water reducing agent is a melamine-based high-efficiency water reducing agent or a polycarboxylic acid-based high-performance water reducing agent.
[0017] Furthermore, the reinforcing agent is nano calcium carbonate or a composite early strength agent.
[0018] The preparation method of the building material comprises the following steps:
[0019] S1: Mix silicate cement, mineral powder, fly ash, water reducing agent, activator, reinforcing agent and water in the above proportions and use a mixer to mix into slurry;
[0020] S2: dilute the composite foaming agent with water at a ratio of 1:10 to allow the foaming agent to foam, and then fully blend with the slurry;
[0021] S3: Add aggregate or light aggregate to the slurry and continue stirring.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention overcomes the technical difficulty of achieving good performance of both light weight and high strength, which are two important indicators that cannot be achieved by traditional concrete components, by improving the concrete raw materials, proportions and preparation methods, breaking the inherent perception in the industry that the density and strength of concrete cannot be taken into account at the same time for many years. DETAILED DESCRIPTION
[0024] The following examples are used to illustrate the present invention, but they are not intended to limit the scope of the present invention.
[0025] In the description of the present invention, unless otherwise specified, "plurality" means two or more than two; the terms "upper", "lower", "left", "right", "inner", "outer", "front end", "rear end", "head", "tail" and the like indicate positions or positional relationships based on the positions or positional relationships shown, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific position, be constructed and operated in a specific position, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third" and the like are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.
[0026] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connection" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0027] Embodiment 1:
[0028] Take 18 parts of 42.5 ordinary Portland cement, 4 parts of mineral powder, 93 parts of fly ash, 2 parts of activator, 9 parts of composite foaming agent, 0.36 parts of water reducer, 0.4 parts of reinforcing agent, and 36 parts of water to obtain a density of 1150kg / m 3 , the compressive strength of lightweight concrete products shall not be less than 10 MPa.
[0029] Implementation steps:
[0030] 18 parts of 42.5 cement, 4 parts of mineral powder, 93 parts of fly ash, 0.36 parts of water reducer, 2 parts of activator, 0.4 parts of reinforcing agent, and 36 parts of water are mixed into a slurry using a mixer.
[0031] Dilute 0.5 parts of composite foaming agent with water at a ratio of 1:10, use a foaming machine to foam, and pump it to the mixer to fully blend with the slurry.
[0032] Pour into the mold box, cover with plastic film and send to the curing bin for natural curing. The temperature in the curing bin should not be lower than 30 degrees Celsius.
[0033] De-mould after 12 hours.
[0034] Fly ash, also known as fly ash, is a fine solid particle in the flue gas ash produced by coal combustion, such as the fine ash collected from the flue gas of a thermal power plant. It reacts with cement hydration to produce calcium hydroxide, which undergoes a secondary reaction to adjust the hydration heat temperature and improve the workability and durability of the building material.
[0035] Performance comparison case:
[0036]
[0037] Embodiment 2:
[0038] Take 22 parts of 42.5 ordinary Portland cement, 10 parts of mineral powder, 12 parts of fly ash, 0.7 parts of activator, 2 parts of composite foaming agent, 1 part of water reducer, 0.4 parts of reinforcing agent, 44 parts of graded sand, and 19 parts of water to obtain a density of 1400kg / m 3 , lightweight aggregate concrete products with a compressive strength of not less than 30 MPa and a thermal conductivity of less than 0.3W / (m·K).
[0039] Implementation steps:
[0040] 22 parts of 42.5 cement, 10 parts of mineral powder, 12 parts of fly ash, 1 part of water reducer, 0.7 parts of activator, 0.4 parts of reinforcing agent, and 19 parts of water are mixed into a slurry using a mixer.
[0041] Dilute 2 parts of composite foaming agent with water at a ratio of 1:10, use a foaming machine to foam, and pump it to the mixer to fully blend with the slurry.
[0042] Add 44 parts of graded sand to the slurry and stir at 100 rpm for 1-2 minutes.
[0043] Pour into the mold box, cover with plastic film and send to the curing bin for natural curing. The temperature in the curing bin should not be lower than 30 degrees Celsius.
[0044] De-mould after 12 hours.
[0045] Performance comparison case:
[0046]
[0047] Embodiment three:
[0048] Take 20 parts of 42.5 ordinary Portland cement, 10 parts of mineral powder, 14 parts of fly ash, 0.6 parts of activator, 2 parts of composite foaming agent, 1 part of water reducer, 0.3 parts of reinforcing agent, 30 parts of ceramsite, and 16 parts of water to obtain a density of 1500kg / m 3 , ultra-light aggregate concrete products with compressive strength not less than 45 MPa and thermal conductivity within 0.35W / (m·K).
[0049] Implementation steps:
[0050] 20 parts of 42.5 cement, 10 parts of mineral powder, 14 parts of fly ash, 1 part of water reducer, 0.6 parts of activator, 0.3 parts of reinforcing agent, and 16 parts of water are mixed into a slurry using a mixer.
[0051] Dilute 2 parts of composite foaming agent with water at a ratio of 1:10, use a foaming machine to foam, and pump it to the mixer to fully blend with the slurry.
[0052] Add 30 parts of ceramsite into the slurry and stir at 100 rpm for 1-2 minutes.
[0053] Pour into the mold box or the location where construction is required, cover with plastic film and allow to cure naturally. The ambient temperature should not be lower than 30 degrees Celsius.
[0054] De-mould after 12 hours.
[0055] Performance comparison case:
[0056]
[0057] In order to further verify the effect of the building material of the present invention, a comparative experiment was conducted by removing aggregate and lightweight aggregate, which are raw materials for improving the flexural strength of concrete:
[0058] Comparative Example 1:
[0059] In this embodiment, 15 parts of 42.5 ordinary Portland cement, 15 parts of mineral powder, 100 parts of fly ash, 2.4 parts of activator, 10 parts of composite foaming agent, 0.3 parts of water reducer, 0.4 parts of reinforcing agent, and 45 parts of water are taken to obtain a density of 1050 kg / m 3 , the compressive strength of lightweight concrete products is not less than 8 MPa.
[0060] Comparative Example 2:
[0061] In this embodiment, 40 parts of 42.5 ordinary Portland cement, 40 parts of mineral powder, 10 parts of fly ash, 0.2 parts of activator, 2 parts of composite foaming agent, 0.6 parts of water reducer, 0.2 parts of reinforcing agent, and 26 parts of water are taken to obtain a density of 1750 kg / m 3 , the compressive strength of lightweight concrete products shall not be less than 55 MPa.
[0062] In order to verify the critical range in which the building material of the present invention is superior to ordinary concrete materials, the lightweight concrete was used as a reference to adjust the mix ratio and conduct a limit test:
[0063] Limit test 1:
[0064] Take 40 parts of 42.5 ordinary Portland cement, 15 parts of mineral powder, 25 parts of fly ash, 2.4 parts of activator, 10 parts of composite foaming agent, 0.5 parts of water reducer, 0.4 parts of reinforcing agent, 50 parts of ceramsite, and 45 parts of water to obtain a density of 750kg / m 3 , the compressive strength of lightweight concrete products shall not be less than 2.5 MPa.
[0065] Limit test 2:
[0066] Take 15 parts of 42.5 ordinary Portland cement, 25 parts of mineral powder, 50 parts of fly ash, 2.4 parts of activator, 10 parts of composite foaming agent, 0.5 parts of water reducer, 0.4 parts of reinforcing agent, 30 parts of ceramsite, and 40 parts of water to obtain a density of 750kg / m 3 , the compressive strength of lightweight concrete products shall not be less than 5 MPa.
[0067] Limit test three:
[0068] Take 45 parts of 42.5 ordinary Portland cement, 10 parts of mineral powder, 0 parts of fly ash, 0.4 parts of activator, 2 parts of composite foaming agent, 0.5 parts of water reducer, 0.2 parts of reinforcing agent, 30 parts of ceramsite, and 45 parts of water to obtain a density of 1800kg / m 3 , the compressive strength of lightweight concrete products shall not be less than 7.5 MPa.
[0069] Limit test 4:
[0070] Take 35 parts of 42.5 ordinary Portland cement, 10 parts of mineral powder, 0 parts of fly ash, 0.8 parts of activator, 2 parts of composite foaming agent, 1 part of water reducer, 0.3 parts of reinforcing agent, 30 parts of ceramsite, and 23 parts of water to obtain a density of 1600kg / m 3 , the compressive strength of lightweight concrete products shall not be less than 35 MPa.
[0071] The specific data are shown in the following table:
[0072]
[0073] Table 1
[0074] According to the data in the table, according to traditional concrete materials, the aggregate or light aggregate added to the concrete can be understood as a skeleton as a filler. Our experiments have proved that in this technology, aggregates (sand, gravel, etc.) and light aggregates (ceramsite) in different proportions can improve the flexural strength of the product in a specific formula, and the strength is in the range of 2.0-3.5 MPa. However, by comparing the embodiment with the embodiment, it can be seen that the flexural strength of the concrete without adding aggregates and light aggregates is between 1.0-3.0 MPa, which has little effect on the final compressive strength of parts with a compressive strength below 55 MPa. Therefore, for the construction industry, the materials in the present invention can recycle some construction waste during manufacturing, which is more environmentally friendly.
[0075] As can be seen from the table, when the silicate cement in the component is 15-40 parts and the mineral powder is 4-40 parts, the adjustment of the fly ash content can achieve a higher strength level than lightweight concrete with the same density.
[0076] The building material of the present invention has the following significant advantages and technical effects in specific applications:
[0077] 1. As a lightweight concrete material, it solves the technical disadvantages of traditional concrete materials that they cannot have both low density and high strength. 3 The physical properties of different density levels are compared with those of traditional concrete. The density of traditional concrete with the same volume and the same compressive strength is only 60% of that of traditional concrete. While ensuring a certain compressive strength, lightweight concrete has a significantly lower thermal conductivity and a smaller density than traditional concrete.
[0078] 2. Improve energy efficiency
[0079] 1. Resource recycling: In the production process, a large amount of industrial waste and construction waste can be used as lightweight aggregate to achieve resource recycling, reduce the exploitation of natural resources, and reduce damage to the environment.
[0080] 2. Energy saving and emission reduction: Its lightweight characteristics can reduce energy consumption during transportation. Its good thermal insulation performance also helps to reduce energy consumption during the use of buildings, reduce carbon emissions, and is conducive to achieving energy saving and emission reduction goals in the construction industry.
[0081] 3. Engineering performance optimization
[0082] 1. Reduce the deadweight of the structure: Its density is much lower than that of ordinary concrete, which can significantly reduce the overall weight of the building. In high-rise buildings, it can reduce the bearing requirements of the foundation and reduce the cost of infrastructure construction. In the construction of long-span bridges, it can make the structure lighter and the span larger.
[0083] 2. Good seismic performance: The elastic modulus is low, and it can absorb and disperse energy when impacted, effectively enhancing the seismic resistance of the building and improving its safety in natural disasters such as earthquakes.
[0084] 4. Significant economic benefits
[0085] 1. Reduce overall costs: The weight of the structure is reduced, which can reduce the costs of infrastructure construction and structural reinforcement. At the same time, its production and construction process is relatively simple, which can improve construction efficiency, shorten construction period, and thus reduce the overall project cost.
[0086] 2. Extend service life: It has good durability and can resist the erosion of harsh environment, reduce the number of repairs and replacements of buildings during use, extend the service life of buildings, and further improve economic benefits.
[0087] The embodiments of the present invention are given for the purpose of illustration and description, and are not intended to be exhaustive or to limit the invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described in order to better illustrate the principles and practical applications of the present invention and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.
Claims
1. A building material, characterized in that: The invention comprises the following components in parts by weight: 15-45 parts of silicate cement, 0-40 parts of mineral powder, 0-100 parts of fly ash, 0.2-2.4 parts of activator, 2-10 parts of foaming agent, 0.3-1 parts of water reducing agent, 0.2-0.4 parts of reinforcing agent and 16-45 parts of water.
2. A building material according to claim 1, characterized in that: Among them, 15-40 parts of Portland cement and 4-40 parts of mineral powder.
3. A building material according to claim 1, characterized in that: It also includes 0-100 parts of aggregate and 0-50 parts of light aggregate.
4. A building material as claimed in claim 3, characterized in that: The aggregate includes but is not limited to 3-10 mm crushed stone, construction solid waste, graded sand, etc., and the light aggregate is expanded clay and clay sand.
5. A building material according to claim 1, characterized in that: The silicate cement is silicate cement with a grade of 42.5 or above.
6. A building material according to claim 1, characterized in that: The mineral powder is granulated blast furnace slag powder.
7. A building material according to claim 1, characterized in that: The fly ash is fine solid particles in the flue gas ash produced by coal combustion.
8. A building material as claimed in claim 1, characterized in that: The activator is a base activator.
9. A building material as claimed in claim 1, characterized in that: The foaming agent is a composite foaming agent.
10. A building material according to claim 1, characterized in that: The water reducing agent is a melamine-based high-efficiency water reducing agent or a polycarboxylic acid-based high-performance water reducing agent.
11. A building material according to claim 1, characterized in that: The reinforcing agent is nano calcium carbonate or a composite early strength agent.
12. The method for preparing the building material according to claim 1, characterized in that: The following steps are involved: S1: Mix silicate cement, mineral powder, fly ash, water reducing agent, activator, reinforcing agent and water in the above proportions and use a mixer to mix into slurry; S2: dilute the composite foaming agent with water at a ratio of 1:10, foam the foaming agent, and then fully blend it with the slurry; S3: Add aggregate or light aggregate to the slurry and continue stirring. (Whether to add aggregate or light aggregate depends on the actual needs of the building components).